A Novel Preparation Method for Octreotide Acetate–Loaded PLGA Microspheres with a High Drug‐Loading Capacity and a Low Initial Burst Release, and Its Studies on Relations between In Vitro and In Vivo Release. Issue 3 (1st August 2013) - Chen, Bin; Han, Bing; Song, Liping; Xu, Dan; Pei, Jin
ABSTRACT: In this study, octreotide acetate (OTA)–loaded poly(lactide‐ co ‐glycolide) (PLGA) microspheres were prepared using an optimized double emulsion solvent evaporation method. The loading capacity (LC) was increased by raising the concentration of OTA in the inner aqueous phase (W1), and burst release was decreased (<10.0%) because the higher viscosity hindered the diffusion of OTA. The in vitro release profiles were closely correlated with in vivo release profiles calculated using the Wagner–Nelson method ( r = 0.9876). To evaluate the drug release profiles rapidly, an accelerated release method was developed. In the accelerated release method, the acidic and alkaline buffers (the first 6 h, pH 4.0; the last 18 h, pH 9.6) were used as release media, respectively. Results indicated that the accelerated release profiles (24 h) were closely correlated with the in vivo release profiles ( r = 0.9623). Therefore, through optimization of the experiment variables (buffer components and pH), an accelerated release method was developed to evaluate in vivo drug release from microspheres. © 2013 Wiley Periodicals, Inc. Adv Polym Technol 2013, 32, 21354; View this article online atwileyonlinelibrary.com . DOI 10.1002/adv.21354